Peran Pembelian Spontan dalam Menentukan Citra Merek CafÃ© - Dewanti, Retno; Leonard, Jefry; Tjoe, Tjia Fie (Binus Business Review, 2012)
Cafe employers realize the importance of visual merchandising management to enhance brand image. Visual merchandising is the activity of promoting the sale of representative goods at retail outlets. Previous research showed that attractive displays can produce unexpected purchases regularly. Impulse buying can enhance brand image. The results of this study indicate that brand image is determined by two variables together the virtual merchandising and customer experience. Virtual merchandising and customer experience influence significantly in creating unexpected purchases. The test results of path analysis show that impulse buying was important in moderating visual merchandising and customer experience to determine the brand image. Impulse buying plays a positive and significant role on the formation of brand image.